Estabelecimento e caracterização de um banco de células de trabalho para produção da enzima Taq DNA polimerase - Faria, Surian Guerios (2017)
The Molecular Biology Institute of Paraná (Instituto de Biologia Molecular do Paraná - IBMP) produces diagnostic kits for the Brazilian Unified National Health System (Sistema Único de Saúde - SUS), that consist in molecular tests, carried out by polymerase chain reaction (PCR). This reaction is performed by the enzyme Taq DNA Polymerase (Taq). The IBMP manufactures Taq from bacterial cell culture in accordance with Good Manufacturing Practices (GMP) and intends to produce it from a cell bank using cells from the same clone in order to increase the homogeneity and reproducibility of the production process. The objective of the present work is to establish a working cell bank (WCB) and to evaluate its stability for the production of the Taq enzyme, starting from a master cell bank (MCB) established in BioManguinhos. The WCB establishment consists of cultivating MCB colonies, characterizing them, evaluating performance, and electing proper cells to compose the WCT. The stability study contemplates tests to prove that cells retain the ability to produce Taq over time (i.e., cell viability, plasmid stability, growth kinetics, expression induction, plasmid DNA extraction and dosage, restriction analysis and plasmid evaluation). The decisive discretion for the selection of one of the clones to compose BCT was the result of growth kinetics. Stability was studied in 10 month-to-month evaluations. In them, cell viability was higher than 1,0 x 106 CFU/mL, showing that the cells remain capable of performing their metabolism and reproduction. Growth to the exponential phase occurred between 6 and 7 hours of culture, with a specific growth rate greater than 0.4 min-1 . The cultures with 1 mM IPTG expressed Taq DNA polymerase enzyme, revealing the qualification of the cells to the intended purpose. The plasmid stability was greater than 90%, indicating that the plasmid pBioMTaq remains stable and has good replication ability. The mean plasmid concentration was 338 ng/μL, and in all months it was greater than 100 ng/μL. In the restriction analysis the plasmids were correctly cleaved and in the plasmid evaluation there was adequate amplification of the 500 bp fragment, demonstrating that the plasmid remains intact and stable, with compatible sequences with its construction. The WCB was tested as substrate for a typical IBMP production process of Taq DNA polymerase, presenting satisfactory in all the stages in which it was evaluated. These results indicate that the established bank remained stable over 10 months and is apt to be used as a prototype for a WCB in compliance with GMP.